The effect of corporate governance and financial statement disclosures on company value: A study on publicly listed firms in the Philippines - Altamirano, Geraldine J. (Animo Repository, 2016)
Extensive operations and complex functions intensified the gap between management and their customers and as a means of survival, companies must have the capacity to induce their consumers and to raise company value. Disclosures, in turn, laid the foundation for molding the reputation of the company. These disclosures are what users such as investors and creditors rely on in making decisions about the company. However, notable corporate scandals like Enron, WorldCom and the Lehman Brothers exposed the likelihood of deception and manipulation to be orchestrated by management themselves. The trust between investors and management tumbled down. These led financial governing bodies to strictly implement laws and regulations that firms should adhere to in order to protect the company various stakeholders. With the investor inclination to a justifiable account, management would be publishing information that would enhance the firm value. This study aimed to establish the relationship between corporate disclosures and the firm value using the information from publicly-listed firms in the Philippines. The results of the study showed that financial statement disclosures and company value had no effect on one another for the overall results of all publicly listed companies, however for the inter-industry analysis, there is varying significance per industry. Meanwhile, corporate governance had an effect on financial statement disclosures and company value both for the overall and per industry level.